Political and Party System of Germany after Elections to the Bundestag (2014-2015) - E. P. Timoshenkova (Vestnik MGIMO-Universiteta)
Analyzed in the article is German political party system after the 2013 Bundestag elections. The author studies results of the 2015 elections to the European Parliament and of2014-2015 elections to German federal legislative bodies. European elections are known to be the voters' second priority; but what role do they play for German citizens? The author reveals the voters' motives for taking part in elections and making corresponding decisions, which allows to describe the key patterns and trends of development of elections to the European Parliament. Special attention is paid to the role of smaller parties and assessment of FDP's possible retirement from the German federal political stage. Success of the new right-wing populist party «Alternative for Germany», which succeeded in getting seats not only in the European Parliament, but also in all legislative bodies in German lands where elections took place, makes one consider its prospects and consequences of its emergence for the German political party system. Since its best results were achieved in the East of the country, the article offers thorough analysis of the voters' behavior in so-called new lands. Elections in Hamburg and Bremen have always had special features. People in these lands are more eager to support social democrats, which was proved by the 2015 elections. Could the «choice of the big city» be considered to follow its own logic, and does the CDU have a chance to break this tradition? Attempting to answer with this question, the author turns to the results of a sociological study of the Adenauer Fund, which support the statement that it is the candidate's personality and not the party itself that plays decisive role in the party's victory. In conclusion, the author gives her own interpretation of features of the modern German political party system and a forecast of its future development.